Temperature dependent Raman spectra of CsCdBr3 and CsCdCl3 crystals - Demirbilek, R.; Feile, R.; Bozdogan, A. Celik (ELSEVIER, 2015)
Temperature dependent Raman spectra of the crystals CsCdCl3 and CsCdBr3 grown by Bridgman method were measured in the temperature range of 5-300 K. The description of the line-broadening and the line-shift of the observed Raman lines are mainly based on the anharmonicity due to the phonon-phonon interaction. The analysis of the temperature dependence of the Raman-lines that involve vibrational modes on common sites in both crystals make it possible to compare the anharmonicity of the lattice vibration in both crystals. The breathing mode in both CsCdCl3 and CsCdEr3 crystals is the strongest and comparable mode in this manner. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Raman spectra; CsCdCl3; CsCdBr3; Anharmonicity; RARE-EARTH IONS; SCATTERING; CSMGBR3; PHONONS; PURE; Optics